How Competence, Motivation, and Job Satisfaction Drive Employee Performance - Syarif, Muh.; Nasir, Muhammad; Rina, Rina (International Journal of Business, Law, and Education, 2024)
This study aims to determine how competence, motivation, and job satisfaction affect employee performance at PT Bank Mega, Tbk Makassar Area. The data collection technique was carried out through distributing questionnaires, with the number of samples determined as many as 132 respondents. The data analysis method used is multiple linear regression analysis. The findings of this study indicate that the competency variable has a positive and significant influence on employee performance at PT Bank Mega, Tbk Makassar Area. Work motivation variable has a positive and significant influence on employee performance. Job satisfaction variable also has a positive and significant influence on employee performance at PT. Bank Mega, Tbk Makassar Area.